Options and results in managing suction loss during small-incision lenticule extraction. Issue 7 (July 2021) - Wan, Kelvin H.; Lin, Timothy P.H.; Lai, Kenny H.W.; Liu, Shu; Lam, Dennis S.C.
Abstract : Suction loss, although uncommon, can occur during any stage in SMILE. Successful management depends on understanding the available retreatment options and laser parameters adjustment across the different stages of photodisruption. Abstract : Suction loss is an intraoperative complication in small-incision lenticule extraction (SMILE) that presents a management challenge for the refractive surgeon. The purpose of this review is to evaluate the visual, refractive, and wavefront outcomes after suction loss across the different stages of SMILE with various respective surgical treatments. Surgical management options include immediate re-SMILE by redocking or delayed re-SMILE, with or without adjustment of the laser parameters, conversion to femtosecond laser in situ keratomileusis, transepithelial photorefractive keratectomy, refractive lenticule extraction, or pseudo-SMILE. The restart treatment module on VisuMax provides appropriate retreatment recommendation. Most retreatment options for suction loss, immediate or delayed, resulted in effective, safe, and predictable outcomes, and patients were satisfied with their outcomes. Based on available level II evidence, immediate re-SMILE with or without adjustment to the laser settings achieve favorable visual and refractive outcomes in handling this intraoperative complication across all stages of SMILE.